Experimental investigations of contact-type damage nonlinearity - Klepka, A.; Dziedziech, K.; Pieczonka, Ł.; Adamczyk, M.; Staszewski, W.J. (Journal of physics. Conference series, 2017)
The problem of identification of non-linear phenomena associated with contact-type non-linearity is the subject of many research papers. The number of theoretical models describing the non-linear phenomena is constantly increasing. New capabilities of experimental verification and observation of these non-linear effects provide opportunities for a more accurate mathematical description of the non-linear behavior of contact interfaces. Better understanding of the non-linear related contact mechanisms can lead to more accurate numerical models of structures with contact-types defects, damage propagation and prediction algorithms and development of new methods for damage detection. This paper presents research on the non-linear acoustic phenomena in the presence of contact-type damage. Two test samples in contact are subject to vibro-acoustic modulation test. Non-linear spectral components were analysed and compared to the temperature changes generated as a results of the frictional forces.